Endometrial and cervical cancer: incidence and mortality among women in the Lodz region - Leśniczak, Beata; Krasomski, Grzegorz; Oszukowski, Przemysław; Stetkiewicz, Tomasz; Woźniak, Piotr (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: By the early 21st century the most common cancer of female genitals in Poland was cervical cancer. Now endometrial cancer ranks first. The aim of this study was to analyse the incidence and mortality of endometrial and cervical cancer among women in the Lodz region. Material and methods: Data on the incidence and mortality of endometrial and cervical cancer among inhabitants of the Lodz region were obtained from the National Cancer Registry and Bulletin of Cancer Cases in the Lodz region. The analysis covered ten consecutive years beginning in 2001. Results : The number of new cases reported in 2010 exceeded that observed in 2001 by 181. The standardized incidence rate of endometrial cancer increased by 6.3, while the standardized incidence rate of cervical cancer decreased by 1.4. Conclusions : In the years 2001-2010, the incidence of endometrial cancer increased by 88.3% and that of cervical cancer decreased by 6.5% among inhabitants of the Lodz region. In the years 2001-2010, mortality of endometrial cancer increased by 24.5% and that of cervical cancer decreased by 12.6%. In 2010, the highest crude incidence rates in the Lodz region of both endometrial and cervical cancer at 39.1 were recorded in the district town of Piotrków.